Figure 161. Diagram of an Electric Telegraph System - Croft, Terrell (Practical Electricity, 1917)
Diagram depicting an electric telegraph system running between the cities of Richmond, Virginia, Philadelphia, Pennsylvania, and New York, New York.
Keywords: Communication; Communication and technology; Electrical engineering; Electricity; Telecommunication; Telegraph; Telegraph lines